Web-Based Assessment System for Graduate Learning Achievements in Outcome-Based Education - Alek Wijaya; Wahyu Pranata; Ahmad Syazili; Siti Sauda (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
This research utilizes the Rapid Application Development (RAD) approach, with the analysis stage involving a review of relevant literature and interviews with prospective system users. The next stage is the requirement planning, which entails defining the features or services within the software accessible to prospective system users. The design phase employs use case diagrams, activity diagrams, and Entity Relationship Diagrams (ERD). Subsequently, it is translated into the Laravel framework and undergoes testing to produce a software system for assessing Graduate Learning Outcomes (CPL). This system offers facilities for academic programs to create outcome-based education (OBE) mappings and enables instructors to assess students based on the established mapping data. It also provides students with the ability to view their outcome results. CPL refer to the essential skills that students must acquire following their academic studies. These skills encompass the internalization of grades, attitudes, general knowledge, and specific skills, which students are required to fulfill throughout their academic journey. Outcome grades, as mapped, are attained by students through participation, written tests (quizzes), observations (practical exercises), performance (presentations), mid-term exams, final exams, and oral tests (group assignments). This Graduate Learning Outcomes assessment software is expected to assist program administrators and instructors in managing CPL and also enable students to access detailed records of their outcome grades.